1990
DOI: 10.1073/pnas.87.22.8825
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Paramecium axonemal tubulin into higher plant cells reveals functional sites of microtubule assembly.

Abstract: Incorporation of Paramecium axonemal tubulin into lysed endosperm cells of the higher plant Haemanthus enabled us to identify sites of microtubule assembly. This exogenous Paramecium tubulin could be traced by specific antibodies that do not stain endogenous plant microtubules. Intracellular copolymerization of protozoan and higher plant tubulins gave rise to hybrid polymers that were visualized by immunofluorescence and by immunoelectron microscopy. The addition of exogenous tubulin revealed many free ends of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(46 citation statements)
references
References 31 publications
3
43
0
Order By: Relevance
“…33]. However, the plus ends of the interdigitating MTs have to be positioned at the phragmoplast midzone to define the destination of vesicle transport.…”
Section: Current Opinion In Plant Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…33]. However, the plus ends of the interdigitating MTs have to be positioned at the phragmoplast midzone to define the destination of vesicle transport.…”
Section: Current Opinion In Plant Biologymentioning
confidence: 99%
“…When two genes encoding functionally redundant Kinesin-12 motors are mutated, the phragmoplast MT array no longer forms a defined midzone [31]. MT polymerization continues at the plus ends after the anti-parallel MTs are cross-linked by MAP65-3 [32,33]. However, the plus ends of the interdigitating MTs have to be positioned at the phragmoplast midzone to define the destination of vesicle transport.…”
Section: Anti-parallel Mts In the Phragmoplastmentioning
confidence: 99%
“…The nuclear envelope may temporarily nucleate Mts at a particular stage of the cell cycle (Falconer, Donaldson & Seagull, 1988;Seagull, 1989;Vantard et al, 1990;Palevitz, 1991). A similar temporal relationship between cell plate formation and daughter nuclei reconstitution exists in the cell types examined here and the cells of the moss Sphagnum (Schnepf, 1973 ; see also Steer, 1984), an event which could explain the cortical reappearance of the cortical Mts in these plants.…”
Section: Reestablishment Of Cortical Mtsmentioning
confidence: 99%
“…This suggests that MTs are nucleated from the distal ends and polymerized toward the division site. However, in permeabilized tobacco (Nicotiana tabacum) cells and Haemanthus endosperm cells, exogenous tubulins were incorporated into the phragmoplast overwhelmingly in its midline (Vantard et al, 1990;Asada et al, 1991). These studies also showed that newly polymerized MTs overlapped and then slid outward.…”
Section: Introductionmentioning
confidence: 99%